1999
DOI: 10.1136/thx.54.10.917
|View full text |Cite
|
Sign up to set email alerts
|

Increased carbon monoxide in exhaled air of patients with cystic fibrosis

Abstract: Background-Inflammation, oxidative stress, and recurrent pulmonary infections are major aggravating factors in cystic fibrosis. Nitric oxide (NO), a marker of inflammation, is not increased, however, probably because it is metabolised to peroxynitrite. Exhaled carbon monoxide (CO), a product of heme degradation by heme oxygenase 1 (HO-1) which is induced by inflammatory cytokines and oxidants, was therefore tested as a noninvasive marker of airway inflammation and oxidative stress. Methods-Exhaled CO and NO co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
57
3

Year Published

2001
2001
2022
2022

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 89 publications
(61 citation statements)
references
References 43 publications
1
57
3
Order By: Relevance
“…Thus, although marker levels in ex-smoker subjects should be interpreted with caution, smokers can be reliably discriminated from exsmokers using this device. Consequently, this eCO measurement methodology is widely accepted by experts on this field of research (12,13,21,26,(29)(30)(31)(32).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Thus, although marker levels in ex-smoker subjects should be interpreted with caution, smokers can be reliably discriminated from exsmokers using this device. Consequently, this eCO measurement methodology is widely accepted by experts on this field of research (12,13,21,26,(29)(30)(31)(32).…”
Section: Discussionmentioning
confidence: 99%
“…Increased concentration of eCO has been demonstrated in several inflammatory lung diseases including asthma (12), bronchiectasis (13), and cystic fibrosis (CF) (21). Several recent studies have reported the elevated levels of eCO in COPD as well (18,20).…”
Section: Introductionmentioning
confidence: 99%
“…The levels of exhaled CO are increased in patients with bronchiectasis and it is not reduced in patients treated with inhaled corticosteroids [46]. In cystic fibrosis (CF) there is an increase in the level of exhaled CO and this is further increased during infective exacerbations [47,48]. While in patients with stable CF inhaled steroids do not appear to affect the level of CO, oral corticosteroids are associated with lower values.…”
Section: Exhaled Carbon Monoxide In Lung Diseasesmentioning
confidence: 98%
“…Recently, Montuschi (54 ) reviewed EBC analyses in patients with COPD and listed related breath markers, including H 2 O 2 , eicosanoids (leukotrienes, prostanoids, and isoprostanes), NO-derived products (S-nitrosothiols, nitrite, and nitrate), pH, aldehydes, and others. Moreover, CO has also been studied as a breath marker of asthma (55)(56)(57) and CF (58,59 ); H 2 O 2 as a breath marker of asthma (60,61 ), COPD (62,63 ), and CF (64,65 ); isoprostanes as breath markers of asthma (66 ), COPD (67 ), and CF (68 ); and nitrite/nitrate as breath markers of asthma (69 ) and CF (70,71 ).…”
Section: Lung Diseasesmentioning
confidence: 99%